PEMBUATAN INFOGRAFIS DUSUN KRAJAN I - Dwipraptono Agus Harjito (Asian Journal of Innovation and Entrepreneurship, 2015)
Citizen need to know statistics of their area, but not all citizens are able to understand the statistics in the form of numbers, which is complicated, it needs to betranform into an infographic. Then, writer perform community service in the form ofmaking infographics to illustrate the condition of dusun Krajan.